Formulation, stability study and preclinical evaluation of a vaginal cream containing curcumin in a rat model of vulvovaginal candidiasis - Fernandes, Ligia de Souza [UNESP]; Amorim, Yuri Martins; Silva, Elton Liberio da; Silva, Samuel Calixto; Aparecida Santos, Alecia Junia; Peixoto, Franciele Natalia; Neves Pires, Luara Moniele; Sakamoto, Raquel Yumi; Horta Pinto, Flavia do Carmo; Costa Scarpa, Maria Virginia [UNESP]; Freitas Araujo, Marcelo Gonzaga de (Wiley-Blackwell, 2018)
Owing to the growing resistance among isolates of Candida species to usual antifungal agents and the well-known therapeutic potential of curcumin, the purpose of this study was to develop and validate a vaginal formulation containing this substance and to evaluating its effectiveness in the treatment of experimental vulvovaginal candidiasis. Curcumin was incorporated in a vaginal cream in three concentrations (0.01%, 0.1% and 1.0%). The different concentrations of the cream and its controls were intravaginally administered in an immunosuppressed rat model to evaluate the efficacy in the treatment of experimental vulvovaginal candidiasis. Samples of the cream were also subjected to centrifugation and physical stability tests and an analytical method for quantification of curcumin was validated based on HPLC. The formulation was stable and the HPLC method could be considered suitable for the quantitative determination of curcumin in the cream. After 6days of preclinical study, the number of infected animals was 1/6 in all groups treated with curcumin vaginal cream and the fungal burden showed a progressive reduction. Reduction in the inflammatory infiltrate was observed in the group treated with 1.0% cream. Vaginal cream containing curcumin could be considered a promising effective antifungal medicine in the treatment of vulvovaginal candidiasis.
Keywords: analytical method validation; antifungal; Candida albicans; Curcumin; stability study; vaginal cream; vulvovaginal candidiasis